Genetic and Gender Influences on Hypertrophic Cardiomyopathy: A Comprehensive Population-based Study of Clinical Outcomes and Implications - Chhabra, Shibba Takkar; Singal, Gautam; Gupta, Anshuman; Aslam, Naved; Wander, Gurpreet Singh; Goyal, Abhishek; Batta, Akash; Tandon, Rohit; Mohan, Bishav (International journal of applied and basic medical research, 2025)
Background: Hypertrophic cardiomyopathy (HCM), associated with left ventricular hypertrophy, can lead to significant morbidity. Given the hereditary association, identifying population-specific genetic markers and gender disparities could enable better screening and management strategies. Aim: The study aimed to observe the genetic patterns of HCM and investigate its gender associations among the Indian population. Methodology: A prospective analysis was performed based on the medical records of patients with HCM. Genetic testing was conducted among those with a family history of HCM or sudden cardiac death. Genetic testing results, echocardiography, and clinical outcomes were documented. The prevalence of HCM types and genetic abnormalities were estimated in the study population and were compared between the two genders. Results: The study included 103 patients with a mean age of 56.3 ± 13.9 years. Genetic analysis was conducted in 48/103 individuals based on the hereditary linkage. Only 50% of the 48 individuals had known genes associated with HCM. About 48% had apical or midapical HCM, and 31.1% had reverse curvature HCM. About 38% of apical and 60% of neutral or reverse curvature were associated with genetic abnormalities. The more commonly associated genes were MYBPC3 and MYH7. The current study also identified genetic variants in several emerging genes in Indian HCM patients. Conclusion: Our study findings indicate that the prevalence of different types of HCM is different in the Indian population. With only 50% of the hereditary HCM linked to known genes, the study calls for further screening of genes associated with HCM in the Indian population.